PHARMACOLOGICAL POTENTIAL OF MATRICARIA RECUTITA-A REVIEW (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Matricaria recutita, once it has been called as Marticaria chamomilla, Chamomilla recutita, and Chamomilum nobile family Asteraceae. The main constituents of this plant include the terpenoids α-bisabolol and its oxides and azulenes, including chamazulene. Matricaria recutita shows different pharmacological activities like anti-inflammatory, anti- cancer, treatment of stress and depression, anti-allergic etc. This review focuses on the detailed chemical constituents, pharmacological activities of different parts of this plant.